Performance trajectories of Italian professional cyclists: an analysis of the influence of youth performance on professional success - Filipas, L.; Vecchi, S.; Codella, R.; Boccia, G.; Brustio, P. R. (International Journal of Performance Analysis in Sport, 2025)
The aim of the study was to analyse individual performance trajectories of professional (PRO) Italian cyclists across their careers. It sought to compare the performance progression of successful and unsuccessful PRO cyclists, analyse the best predictors of success in PRO cyclists and explore whether the relative age effect (RAE) influences PRO success. The national ranking positions gathered in the youth (U19 and elite/U23) and the PRO categories were retrieved for every year of competition of 81 PRO Italian cyclists and retrospectively analysed. Participants were divided in successful and unsuccessful, depending on whether they reached at least once the top 400 positions in the PRO ranking or not. Successful PRO cyclists display better youth ranking positions and tend to spend less time in youth categories, transition to the PRO category at an earlier age, reach their best PRO ranking at an older age compared to unsuccessful PRO cyclists. The best youth ranking, the age of the best PRO ranking and the years spent in youth categories are all predictors of PRO success. For every additional year spent in youth categories, there are 50.8% less odds of becoming a successful PRO cyclist. RAE does not affect Italian cyclists` PRO success.